Efektivitas Perencanaan Alat Utama Sistem Persenjataan dalam Memenuhi Kebutuhan Pokok Tentara Nasional Indonesia - Yudha, Rielman; Simatupang, Haposan; Susanto, Tommy Arief (Mahesa Research Center, 2024)
This study analyzes the effectiveness of planning the Main Equipment of the Weapon System (Alutsista) in meeting the operational needs of the Indonesian National Army (TNI). This study uses a qualitative method with the participation of 15 resource persons, including TNI representatives from various forces and defense experts with more than 10 years of experience. Semi-structured in-depth interviews were used to explore the main challenges in the planning of the Defense Equipment, supported by the analysis of related documents and literature. The results of the study identified three main challenges: budget constraints, ineffective inter-agency coordination, and evolving operational needs. Indonesia's defense budget, which is only 0.8% of GDP, shows a significant gap compared to neighboring countries, such as Singapore (3.2%). In addition, the lack of coordination mechanisms between the Ministry of Defense, the TNI, and local industries has led to inefficiencies in the procurement and maintenance of defense equipment. The impact of this challenge includes the limited operational readiness of the TNI, especially in Military Operations for War (OMP) and Military Operations Other than War (OMSP). The study recommends budget optimization of up to 1.5% of GDP, the establishment of an inter-agency integrated working team, and the integration of modern technologies such as drones, big data, and artificial intelligence in the planning of defense equipment. The implementation of these measures is expected to increase the effectiveness of the planning of the Defense Equipment in supporting the main tasks of the TNI and strengthening state sovereignty amid dynamic geopolitical challenges.